Forest structure, species traits and rain characteristics influences on horizontal and vertical rainfall partitioning in a semiarid pine-oak forest from Central Mexico - Pérez-Suárez, M.; Arredondo-Moreno, J. T.; Huber-Sannwald, E.; Serna-Pérez, A. (Ecohydrology, 2014)
ABSTRACT Changes in species composition and abundance driven by land use change may alter canopy and litter characteristics of forests, and thereby modify rainfall redistribution and hydrological processes. To elucidate the interacting effects between tree species traits, forest structure and annual rainfall patterns on hydrological processes, three types of forest assemblages were selected in a semiarid forest of pine–oak in central northwest Mexico. Forest assemblages included monospecific and mixed patches of Quercus potosina and Pinus cembroides. Total precipitation, throughfall, stemflow and runoff were measured from June 2006 to July 2009. Additionally, tree and litter characteristics were measured. Forest traits played an important role differentiating volumes of each fraction among the three forest patches. Throughfall was 15% greater in Q. potosina than in the other forest patches (P < 0.01) and only occurred with rainfall events larger than 1.4 mm for all patch types, whereas Q. potosina stemflow was >20% larger compared with the other two forest patch types (P < 0.01) and occurred following rain events of at least 4.6 mm. Runoff exhibited divergences among forest patches (P > 0.05) that were related to both the litter decomposition stage and the capacity of litter bed to store water. Thus, Q. potosina litter layer exhibited the largest water holding capacity (62%) and P. cembroides (46%) the least. Hence, surface runoff for Q. potosina was seven times lower than that in P. cembroides patches. This study revealed tree trait effects on water fluxes that might have consequences on the dynamics and productivity of semiarid forests. Copyright © 2013 John Wiley & Sons, Ltd.